Nadia Carney: capstone - Carney, Nadia, artist (Colorado State University. Libraries, 2021)
The artist's statement: Trying the things I have never tried before is constantly what drives me. I am drawn to do the things I don't know how to do easily. I am inspired by my thoughts and dreams which are sometimes unrelatable to anything I've ever seen or heard of before. I like to be confused, and confusing. My work often focuses on material exploration and experimentation, leaving people wondering if I am really the one who produced it. What is deep on the inside of me is what only comes out through my art. Expressing myself has never been through words and I believe I am better represented that way. Sometimes there is a subject matter, but most of the time it is just what I like, or an interesting accident. Creating and making are on my very short list of things I really like to do. I know I am going to make something happen as soon as I imagine it, and I want it to be intriguing to others. I wouldn't say I have much of a set style in any medium, but I am drawn to bright and contrasting color themes as well as clean cut shapes and outlines.
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.
Keywords: graphic design